PRACTICES FOR A MACHINE CULTURE: A CASE STUDY OF INTEGRATING CULTURAL THEORY AND ARTIFICIAL INTELLIGENCE - Sengers, Phoebe (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1999)
In taking into account the contemporary development of technology, the author defends an integration of cultural theory and artificial intelligence research into what she calls cultural informatics. The author reviews the history of artificial intelligence from classical to what is now called alternative artificial intelligence research. A small but active community of researchers focusing on critical technical practices has developed in artificial intelligence research; among other items, they have questioned the traditional understanding of an agent as involved in purely logical and formal relations in order to take into account the embodiment of the agent.